Effectiveness of Extracorporeal Shockwave Therapy in the Treatment of Chronic Insertional Achilles Tendinopathy - Siwadol Pinitkwamdee (2020)
© The Author(s) 2020. Background: Extracorporeal shockwave therapy (ESWT) has been proposed as a conservative treatment for insertional Achilles tendinopathy from limited evidence without placebo controls. Our objective was to assess the effectiveness of ESWT compared with sham controls in chronic insertional Achilles tendinopathy. Methods: A double-blind, randomized sham-controlled trial was conducted between 2016 and 2018. The inclusion criteria were patients aged 18 to 70 years diagnosed with chronic insertional Achilles tendinopathy who failed standard conservative treatment. After computerized randomization, patients were allocated into either low-energy ESWT or sham control. Pain, function, and other complaints were assessed using visual analog scale (VAS) and VAS foot and ankle (VAS-FA) at preintervention and weeks 2, 3, 4, 6, 12, and 24. Intention-to-treat analysis and repeated measurement were performed using STATA 15.0. Results: Sixteen patients in ESWT and 15 patients in sham control groups had nonsignificant different baseline characteristics with preintervention VAS (6.0 ± 2.6 vs 5.2 ± 2.2) and VAS-FA (64.8 ± 16.6 vs 65.3 ± 12.7). There was no significant difference in VAS, VAS-FA, and its domains in the long term between the 2 groups. In addition, the ESWT group had significant improvement in VAS (2.9 ± 2.2) at weeks 4 to 12, and sham controls group had significantly improved VAS (2.3 ± 2.6) at weeks 12 to 24. Complications were found only after ESWT treatment. Conclusion: There was no difference at 24 weeks with the use of low-energy ESWT for chronic insertional Achilles tendinopathy, especially in elderly patients. However, it may provide a short period of therapeutic effects as early as weeks 4 to 12. Level of Evidence: Level I, randomized controlled study.